Is Single Cord Irradiation Going to Be a New Standard for T1a Glottic Carcinoma? - Kocak Uzel, Esengul; Figen, Metin; Uzel, Ömer Erol (Frontiers in Oncology, 2020)
Purpose and Objective: To evaluate the disease-free survival, overall survival, dosimetric, and voice handicap index (VHI) results of T1a glottic invasive squamous cell carcinoma (SCC) patients who underwent hypofractionated single vocal cord irradiation (HSVCI). Materials and Methods: The data of 18 patients with stage T1a glottic SCC were collected prospectively and analyzed retrospectively between July 2016 and July 2019. Patients were immobilized using a custom-fitted thermoplastic face and shoulder mask in hyperextension position. The CT scan was performed with 1-mm-thick slices. A planned target volume (PTV) margin of 3 mm was given to clinical target volume (CTV) in all directions, and 13 organs at risk were identified. Patients were prescribed a total of 5760–5808 cGy in 15–16 fractions. Patients had daily cone-beam computed tomography (CBCT), and the treatment was carried out with the physician. VHI test was applied to patients before and at the end of radiotherapy (RT) and 1, 2, 3, 4, and 6 months after the completion of RT. Results: Local control and overall survival rate is 100% for a median of 18 months (6–44 months) of follow-up. A patient was diagnosed with 2nd primary lung cancer and active treatment still continues. All patients completed the treatment within the scheduled time. Grade 1–2 dysphagia and dermatitis occurred in all patients, and no grade 3 and above side effects were observed. The mean values of VHI were 37.00, 39.83, 38.28, 17.17, 12.22, 8.56, and 6.06 at the beginning of RT, at the end of RT, and 1, 2, 3, 4, and 6 months after RT, respectively. Conclusion: Compared to surgery and conventional laryngeal radiotherapy, HSVCI is an alternative treatment method for T1a glottic cancer by reducing the treatment time to 3 weeks, facilitating recurrence treatment, and providing effective sound quality without compromising local control. Considering that ~80% of recurrences in glottic cancer occur within the first 2 years, 100% local control in a median of 18 months is extremely successful, but long-term follow-up is essential to observe possible late side effects.